Socialization of the Law Animal Livestock and Health Prevention of Productive Female Cattle Slaughter in Tebo District - Patriani, Peni (Talenta Publisher Universitas Sumatera Utara, 2019)
Tebo is a district in Jambi Province. The population of beef cattle in 2017 was recorded 17,180 heads reduced by -8.08% from 2016 which was recorded 18,690 heads. The population of buffalo cattle in 2016 was recorded at 10,300 heads reduced by -2.37% to 10,056 heads in 2017. The Factors that causes the population of ruminant animals to decrease is a slaughter, beef cattle disease, death and traffic beef cattle. Solution these problems, needed for socialization to the community and farmer groups about Law No 41 of 2014. Socialization aims to prevent the slaughter of productive female cattle, is expected to increase the population in the meat self-sufficiency program. For prevention of cattle, disease is vaccination socialization in Tebo District. The method used is a lecture, question, and answer. The purpose of socialization is to make community active in the development of livestock populations. Targets in this community service are farmers, communities and farmer groups in Tebo District. Farmer groups included were 12 groups. An output of this community service program is the improvement of farmers' knowledge and technology so that increase the participation of farmers in accelerating the meat self-sufficiency program.